Potential of Fish Farming in Floodplain: A Systematic Literature Review - Khusnul Khotimah; Ferdinand Hukama Taqwa; Marini Wijayanti; Dade Jubaedah (Universitas Muhammadiyah Palembang, 2025)
Floodplain wetlands are important inland water ecosystems with considerable potential for aquaculture development in Indonesia. These ecosystems, characterized by dynamic hydrological conditions and high biodiversity, support a wide variety of native and introduced fish species. This study employs a Systematic Literature Review (SLR) following the PRISMA protocol to examine the ecological, socio-economic, and policy factors that influence the feasibility of aquaculture in floodplain wetlands. Using the Publish or Perish (PoP) software and the Google Scholar database, a total of 996 articles published between 2020 and 2025 were reviewed, and 20 high-quality studies were selected for the final analysis. A systematic literature review indicates that floodplain wetlands possess substantial ecological and economic potential for sustainable fish farming, particularly for local species adapted to flood dynamics. The success of sustainable management is largely determined by the application of adaptive management approaches, the strengthening of community-based governance, and the adoption of innovative practices aligned with wetland ecosystem characteristics. However, existing studies remain limited in addressing long-term monitoring, industrial-scale feasibility, and the impacts of climate change and land-use conversion, highlighting the need for further research.